2014
DOI: 10.7196/samj.7542
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oral and oropharyngeal human papillomavirus in a sample of South African men: A pilot study

Abstract: Background. Human papillomavirus (HPV) infection is well known to be associated with head and neck cancers (HNCs). HPV-associated HNCs are related to sexual behaviour, particularly the lifetime number of oral sex partners, but the epidemiology of oral and oropharyngeal HPV in South African men has not yet been studied. Objectives. To determine the oral and oropharyngeal HPV strain prevalence and associated factors in a selected male population in Pretoria, South Africa (SA). Methods. Male factory workers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 33 publications
4
34
0
Order By: Relevance
“…They found a 5.6% prevalence rate of HPV infection with only two showing high risk genotype 16 or 68. Notably, the survey concluded oral sex was an uncommon practice for the majority of the study participants, but both men with high risk HPV participated in oral sex [28]. Though this study is limited and within a specific population in neighboring South Africa, it does suggest a much more limited practice of oral sex in the region and may help explain the lack of HPV positive tumors in this study.…”
Section: Discussionmentioning
confidence: 83%
“…They found a 5.6% prevalence rate of HPV infection with only two showing high risk genotype 16 or 68. Notably, the survey concluded oral sex was an uncommon practice for the majority of the study participants, but both men with high risk HPV participated in oral sex [28]. Though this study is limited and within a specific population in neighboring South Africa, it does suggest a much more limited practice of oral sex in the region and may help explain the lack of HPV positive tumors in this study.…”
Section: Discussionmentioning
confidence: 83%
“…Further studies are needed to determine whether oro-pharyngeal tumours containing non-HPV-16 high-risk types present less often with lymph node metastases and have better treatment outcomes [33, 37]. Davidson et al [38] reported a HPV prevalence of 5.6 % in oral rinse and gargle samples among male factory workers in Pretoria, South Africa, aged 17 - 64 years. Although oral sex was not common in this population, it was practised among men identified with HR-HPV infection [38].…”
Section: Discussionmentioning
confidence: 99%
“…Davidson et al [38] reported a HPV prevalence of 5.6 % in oral rinse and gargle samples among male factory workers in Pretoria, South Africa, aged 17 - 64 years. Although oral sex was not common in this population, it was practised among men identified with HR-HPV infection [38]. Performing oral and oro-anal sex on men and women were not associated with oro-pharyngeal HPV infections in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Oral and oropharyngeal HPV in a sample of SA men [9] Oral human papillomavirus (HPV) infection, and specifically HPV type 16 infection, causes up to a 50-fold increase in HPV-positive oropharyngeal squamous cell carcinoma (OSCC). The tumour may originate in the soft palate, tongue base, pharyngeal walls or tonsils.…”
Section: To Frack or Not To Frack?mentioning
confidence: 99%